Open Educational Resources and Open Access Publishing in Higher Education: Policies, Challenges, and Collaborative Models - Anjali Dashrath Kale (International Journal of Trends in Humanities, 2026)
Open Educational Resources (OER) and Open Access (OA) publishing are transforming higher education by promoting equitable access to knowledge, reducing costs, and fostering collaborative innovation. While OER focus on openly licensed teaching and learning materials, OA ensures unrestricted online access to scholarly research. Together, they form an integrated open knowledge ecosystem aligned with global policy frameworks such as the UNESCO OER Recommendation (2019) and the Budapest Open Access Initiative. This study critically examines institutional policies, sustainability strategies, and collaborative models that influence the adoption and long-term implementation of OER and OA in higher education. Using a qualitative, integrative review methodology, the study synthesizes literature published between 2002 and 2024, along with international declarations and institutional reports. The findings indicate that although OER and OA contribute significantly to affordability, visibility, and pedagogical flexibility, institutions face persistent challenges related to funding sustainability, version control, technological infrastructure, faculty engagement, and equity in access. Furthermore, financial models such as Article Processing Charges (APCs) may reproduce inequalities in research dissemination. The study proposes a strategic institutional framework that integrates governance policies, repository development, digital infrastructure, quality assurance mechanisms, and collaborative consortia. It concludes that coordinated institutional commitment, policy alignment, and cross-institutional partnerships are essential to building sustainable and inclusive open knowledge ecosystems, particularly in developing country contexts. Findings highlight that while institutional support and collaborative ecosystems are critical drivers, issues of quality assurance, technological infrastructure, and long-term sustainability remain pressing concerns. A strategic blend of policy frameworks, partnerships, and innovative platforms is essential to strengthen the global OER movement.
Keywords: Collaborative Models; Digital Repositories; Institutional Policy; Open Access Publishing (OA); Open Educational Resources (OER); Sustainability; higher education